Ill-treatment and torture by police officers from the perspective of the Public Prosecutor: Proceedings of the Public Prosecutor in pre-investigation and investigation - Krstić, Gordana Z (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
This paper analyzes the criminal offense of ill-treatment and torture in cases where there are grounds for suspicion that it was committed by police officers. According to the European Convention on Human Rights, the prohibition of torture is an inviolable and absolute right and states have not only a positive obligation to implement norms on the prohibition of torture in their legislation, but also a negative obligation to refrain from applying any form of abuse, but also a procedural obligation to conduct an effective, adequate and urgent investigation. In the domestic legal system, the investigation is conducted by the public prosecutor.  The key factors for the efficiency of the public prosecutor in the criminal proceedings against the accused police officers include the existence of functional cooperation and coordination between the public prosecutor and the unit responsible for internal police control, quickly collecting various types of evidence, and above all documentation, video recording and declarations of all involved persons. The investigation should lead to the identification of suspects, the determination of the sequence of circumstances that preceded a certain criminal event, excluding any form of passive behavior. However, in addition to effectiveness, adequacy and urgency in order to achieve the goals of the investigation, it is necessary to ensure independence and the public prosecutors who conduct the investigation must have a neutral and independent attitude in relation to the suspected police officers. Regardless of the numerous challenges faced by public prosecutors during proceedings in cases of ill-treatment and torture against police officers, their effective and decisive actions have crucial role in solving these type of cases and in strengthening of legal certainty in the sphere of application of Article 3 of the Convention, and even modest advances in a positive sense are reflected in the suppression of torture.